2006
DOI: 10.1038/sj.bjc.6603098
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin expression in colorectal carcinoma is protective and correlates with survival

Abstract: Thrombomodulin (TM) is an endothelial receptor that exhibits anticoagulant, antifibrinolytic and anti-inflammatory activity by inhibiting thrombin and cellular adhesion. In this study, the expression and significance of TM was examined in primary colorectal cancer and its prognostic implications explored. TM immunostaining was performed on formalin-fixed, paraffin-embedded tissue sections, from primary lesions of 200 patients with colorectal carcinoma. Institutional Ethical approval was granted and clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…We also found that A2058 cells stably expressing ectopic TM induced closely clustered colonies, reminiscent of mesenchymal-epithelial transition. The effect of TM in promoting epithelial morphogenesis is consistent with the clinical observations that reduced TM expression is associated with poor prognosis for patients with tumor metastases in lung (31), breast (24), and colorectal (16) cancer. These data suggest that TM may play a negative regulatory role in tumorigenesis by modulating the assembly of cell junctions.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…We also found that A2058 cells stably expressing ectopic TM induced closely clustered colonies, reminiscent of mesenchymal-epithelial transition. The effect of TM in promoting epithelial morphogenesis is consistent with the clinical observations that reduced TM expression is associated with poor prognosis for patients with tumor metastases in lung (31), breast (24), and colorectal (16) cancer. These data suggest that TM may play a negative regulatory role in tumorigenesis by modulating the assembly of cell junctions.…”
supporting
confidence: 75%
“…6B). Consistent with the reduced TM expression in metastatic tumors (16,24,31), TM knockdown significantly promoted the invasive ability of cells immunoprecipitated with an antibody to Snail, in the absence of antibody (Input), or with an isotype-matched immunoglobulin (IgG). Isolated DNA was purified and analyzed by PCR using primers to the region of the TM promoter.…”
Section: Vol 30 2010 Downregulation Of Tm Induces Tumorigenesis 4773mentioning
confidence: 73%
See 1 more Smart Citation
“…[3][4][5][12][13][14] TM has been implicated in cancer biology through several studies showing that TM expression within tumor tissue correlates with a better prognosis for multiple cancers. 12,[15][16][17] Other studies have suggested that modifying TM expression by tumor cells can alter important aspects of the transformed phenotype, including tumor cell migration in vitro and tumor cell proliferation. [18][19][20][21] An influence of nonnative, exogenous TM on cancer biology has also been reported in studies showing that administration of soluble TM limits metastasis in mice.…”
mentioning
confidence: 99%
“…Acquired protein C deficiency is observed in cancer patients, especially in patients using certain types of chemotherapy (Feffer, 1989;Mewhort-Buist, 2008;Rogers, 1988;Woodley-Cook, 2006). The loss of expression of thrombomodulin (or increase in its soluble form), a receptor required to convert protein C to APC, on cancer cells correlates with advanced stage and poor prognosis (Hanly, 2006;Hanly & Winter, 2007;Lindahl, 1993). Low levels of thrombomodulin also increase the invasive ability of cancer cells in vitro (Matsushita, 1998) and is significantly correlated with a high relapse rate in breast cancer (Kim, 1997).…”
Section: Cancermentioning
confidence: 99%